Explaining B decays anomalies in SUSY models. Issue 1 (January 2021) - Boubaa, Dris; Khalil, Shaaban; Moretti, Stefano
Abstract: Recent measurements of certain B decays indicate deviations from Standard Model (SM) predictions. We show that Supersymmetric effects can increase the Branching Ratios (BRs) of both B → Dτντ and B → D*τντ with respect to the SM rates, thereby approaching their newest experimentally measured values.